Weight loss and psychological-related states in high-level judo athletes - Escobar-Molina, R.; Rodriguez-Ruiz, S.; Gutierrez-Garcia, C.; Franchini, E. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
Purpose: This study aimed at comparing weight loss methods (WLM) performed near competition by elite judo athletes from different age and gender groups and relating WLM with the prevalence of eating disorders. Methods: 144 athletes (66 females and 78 males) from the Spanish judo teams participated in this observational descriptive study grouped into cadets, juniors, and seniors. Data were collected during previous training meetings to international tournaments. The used tools are a basic data questionnaire, State-Trait Anxiety Inventory (STAI-T), Food Craving Questionnaire-Trait (FCQ-T), Restraint Scale (RS), and Eating Attitude Test (EAT- 40). Two-way ANOVAs and chi-square tests were used to compare groups. Results: Seniors presented higher use of WLM, especially one week before competition compared with juniors. Judoists were more involved in their diets and reduced more weight as they were older. Females were more concerned about their diets, presented higher anxiety, scored higher in the emotion scale, and more eating disorders symptoms, although weight loss was lower. Anxiety and eating disorders symptoms differences were more common in juniors and cadets, respectively, with higher scores in females. Conclusions and Implications: Seniors seem to develop more effective strategies to cope with weight loss. Cadet and junior females are more likely to suffer from the psychological-related states associated to weight loss. Implications: (1) Educational programs might help competitors and coaches to adopt and promote healthier weight loss processes, (2) special attention should be paid to female young judoists to detect eating disorders in its early stages, and (3) judo organizations should consider implementing new rules to sanction harmful weight loss practices. Originalartikel unter: https://www.researchgate.net/publication/263971141_Weight_Loss_and_Psychological-Related_States_in_High-Level_Judo_Athletes